Application of pulsed plasma streams for materials alloying and coatings modification - Byrka, O.V.; Bandura, A.N.; Chebotarev, V.V.; Garkusha, I.E.; Langner, J.; Sadowski, M.J.; Tereshin, V.I. (Вопросы атомной науки и техники, 2002)
Results of pulsed plasma streams processing of material surfaces with previously deposited FeB and TiAlN coatings are presented. Under the plasma treatment intensive mixing the materials of coating with the material of substrate was achieved. In the first case this provided boronizing of the modified layer with aim of corrosion properties improvement, in the second case – formation of intermediate mixed layer for subsequent deposition of the hard alloyed coatings. Materials alloying with pulsed metal-gas plasma is discussed also.